TOWARDS WOMEN’S EMPOWERMENT IN PERI-URBAN TAMALE: THE ROLE OF SUSTAINABLE MICROFINANCE - Abdul-Razak, A.R; Donkor, S.A; Ansah, I.G.K. (UDS International Journal of Development, 2016)
This study was carried out to investigate the perceptions with respect to the requirments and benefits of microfinance in peri-urban Tamale. A multi-stage sampling technique was employed to select 192 beneficiary and non-beneficiary respondents of microfinance in peri-urban Tamale. Individual Interviews and focus group disccusions were used for the study. The results revealed that the loans were inadequate. Also while 53.7% were satisfied with the interest rate of 25% per annum, 43.2% were not. However, while 87.4% were satisfied with the repayment period, 12.6% were not. Furthermore, 56.8% and 36.8% of respondents had significant and moderate improvements in their businesses respectively. However, 6.3% said that there had not been any change in their businesses. Besides, 71.6% said that their economic status was much better than before. This also impacted positively on their social and political lives. Inadequate credit facilities emerged as the biggest challenge as identified by 52% of respondents. There is the need for governmental support with respect to the inhibiting requrements to increase accessibility without also crippling the Microcredit institutions. Key Words: Microfinance, Women’s Empowerment, Northern Ghana, Peri-urban Tamale